Scoping review: Social support impacts hospital readmission rates. Issue 19 (5th December 2021) - Schultz, Beth E.; Corbett, Cynthia F.; Hughes, Ronda G.; Bell, Nathaniel
Abstract: Aims and objectives: To review and synthesise the current literature on social support and hospital readmission rates. Background: Hospital readmission rates have not declined significantly since 2010 despite efforts to identify and implement strategies to reduce readmissions. After discharge, patients often report the need for help at home with personal care, medical care and/or transportation. Social factors can positively or negatively affect the transition from hospital to home and the extended recovery period experienced by patients. Methods: Published primary studies in peer‐reviewed journals, written in English, assessing the adult medical/surgical population and discussing social support and hospital readmission rates were included. A Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Reviews (PRISMA‐ScR) was completed for this scoping review. Results: The search resulted in 2919 articles. After removing duplicates and reviewing content for the inclusion and exclusion criteria, 23 articles were selected for review. Social support is provided by those within one's social circle. There are several types of social support and depending on the needs to the patient, the type of social required and provided is different. Conclusions: The most common form of social support needed at home for people recovering after a hospitalisation was instrumental support, tangible care in the form of assistance with daily personal and medical care, and transportation. Patients who lacked adequate social support after discharge were at an increased risk of hospital readmission. Relevance to clinical practice: Identifying factors, such as social support, that may impact hospital readmission rates is important for quality hospital to home care transitions. Assessing patients' needs and available social support to meet those needs may be an essential part of the discharge planning process to decrease the risk of hospital readmission.